Are the urgent care services effective for febrile children under five years? A parental and professional perspective. (29th September 2015) - Ranmal, R; Maguire, S; Komulainen, S; Pearse, S; Stephenson, T
Abstract : Aims: Children account for 2.9 million emergency department (ED) attendances/year, and a quarter of NHS Direct calls. The authors wished to explore use of urgent care services by parents of children less than five years, from a parental and professional perspective, framed around the National Institute for Health and Clinical Excellence febrile illness guideline. Methods: Parents using any urgent care service (general practitioner (GP)/walk in centre/out of hours GP/children's admissions unit/ED/other primary care services/ambulance/NHS direct) within Leicestershire, Peterborough, North West London for a febrile child <5 years during January 2009 to June 2009 were approached. Data collected via a parent telephone questionnaire, and the clinical notes. Results: Of 556 parents expressing an interest, 220 enrolled, making 570 contacts (median 3, range 1–13) across all services during this illness, despite the child's episode of illness lasting only 3 days on average. Parents understood local urgent care options, and their first preference was to see a G) (67%; 93/138); and when they were unavailable, NHS Direct (46%; 38/82). Although there were 83 attendances at ED at any point, 49% were advised to do so by another service. 155 made more than one contact involving 505 contacts; 48% (242) of which were initiated by a service provider. Less than 17% of children were "high risk" during the illness, with no deaths. Children were appropriately triaged by the services in 60% of cases. Safety netting was given to 80%; those without this were more likely to re-present than those who did (51% vs 30%, p<0.05) Parents identified a need for precise, consistent, written advice regarding fever and antipyretics. Conclusion: The parents were aware of urgent care service options available, and their first choice was the GP. Multiple contacts are being made, for relatively well children, during self-limiting illnesses, often due to repeated referrals within the system, not initiated by parents. When safety net advice is given, it reduces re-attendances, but parents need more explicit and consistent advice for appropriate home management.